The feedback stability research of HDRI system - Chen, Zhebo; Shen, Chen; Xu, Jin; Ni, Xuxiang; Lu, Zukang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, one kind of high dynamic range imaging (HDRI) system is analyzed and the feedback stability is optimized. In this system, space light modulator (SLM) is used to modulate the input illuminance with the feedback signals. Because of the illuminance uncertainty of the scene, the feedback may take too long or turn into oscillations. To acquire the optimized feedback configuration, PID theory is used to analyze the feedback process. After PID parameter is obtained, simulations are applied to study the parameters. The optimized value range and principle of choice for the feedback control are discussed. Lastly, imaging experiments are conducted to obtain high dynamic range images, and the results prove the validity of PID parameters.
Optica Applicata, Vol. 39, 2009, nr 2, s. 357-363
Keywords: optyka; high dynamic range imaging (HDRI); PID; feedback; imaging